Peran beasiswa zakat indonesia dalam meningkatkan akses pendidikan generasi muda - Fadilah, Deniz Zahratul (Maliki Interdisciplinary Journal, 2026)
The Indonesian Zakat Scholarship serves as one form of utilizing zakat funds aimed at expanding access to education for the younger generation, particularly those from underprivileged communities. This article seeks to examine the role of the Indonesian Zakat Scholarship in helping students obtain more equitable and sustainable educational opportunities. The approach employed in this study is descriptive-analytical, involving a review of various literatures, policies, and practices related to zakat-based scholarship distribution. The discussion reveals that the Indonesian Zakat Scholarship functions not only as financial assistance but also as a means of empowerment that fosters learning motivation, personal potential development, and the formation of social character among beneficiaries. Through educational funding support and accompanying mentoring, this program contributes to reducing disparities in educational access among young people. Therefore, the Indonesian Zakat Scholarship plays a strategic role in supporting educational equity and strengthening the quality of human resources as part of national development.